Study of the Energy Parameters and Possibilities for Modernization of Electric Vehicles for AC Power - Georgy Pavlov (Communications - Scientific letters of the University of Zilina, 2013)
The main problem with thyristor locomotives operated in the country is the low value of the power factor. The paper presents results of a survey of the quality of power consumption in this type of locomotives. Based on the experimental data analyzed, we have determined the main parameters characterizing the traction power consumption. Indicated are some general guidelines for optimization.